The Subaltern and Failed Existential Resistance in Idrus’s Short Story “Kisah Sebuah Celana Pendek” - Waluyo, Isnan; Rizal, Muhammad; Perrodin, David D. (Humanis; Vol 28 No 4 (2024)DO - 10.24843/JH.2024.v28.i04.p03, 2024)
This paper analyzes the short story "Kisah Sebuah Celana Pendek" by Idrus to uncover new interpretations regarding the representation of resistance carried out by colonial subjects or groups. The theoretical framework employed in this study is subaltern theory—an idea referring to groups considered voiceless or incapable of speaking—through a postcolonial critical reading inspired by Gayatri Spivak. The analysis method utilizes deconstruction to open up the possibility of generating new meanings from the discourse. The findings of this analysis reveal that there is resistance against colonial hegemonic power, as represented by Kusno, who stands as a figure of the subaltern. Interestingly, Kusno’s resistance is shaped by an existential inner struggle, manifesting as overt defiance and quiet resistance. Unfortunately, this resistance is ambivalent, as it simultaneously offers hope while exposing the subject’s powerlessness in facing reality. This, in turn, reaffirms the notion that the subaltern is perpetually trapped within the power hegemony.